Early Preterm Infant Feeding Behaviors in Adolescent and Adult Mothers - Supannee Kanhadilok (Asian Journal for Public Opinion Research, 2016)
Background:Adolescent mothers may find the transition to motherhood to be overwhelming when compared to adult mothers. The adaptiveness of mother and infant feeding behaviors may greatly influence the quality of adolescent mothers' feeding interactions when compared to adult mothers.Purpose:To examine the adaptiveness of early maternal and infant feeding behavior between adolescent mothers and adult mothers.Method:In this secondary analysis, six adolescent mothers (< 20 years old) and six adult mothers were videotaped while feeding. The mothers were observed 3 times: when the infants were in the hospital, 1 month old, and 4 months old. The videotapes were coded using four scales of the Parent-Child Early Relational Assessment (PCERA). The two maternal scales were Positive Affective Involvement and Sensitivity/Responsiveness (PAISR) and Regulation of Affect and Behavior (RAB). The two infant scales were Infant Positive Affect, Communication, and Social Skills (IPACS) and Infant Regulation of Affect and Behavior (IRAB). The dyads were videotaped just before hospital discharge and at one and four months corrected age. The Wilcoxon signed-rank test was used to examine the difference in the PCERA between the two groups.Results:Adolescent mothers had a significantly lower score on the PAISR before hospital discharge (p-value 0.005) and at one month corrected age (p-value 0.008) than adult mothers. Adolescent mothers also had a significantly lower score on the RAB before hospital discharge, 1 and 4 months corrected age than adult mothers. There were no significant differences in IPACS and IRAB of infants of adolescent and adult mothers.Conclusion:Clinicians need to be aware of the differences in sensitivity that occur.